Prevalence of the Anterior Occipital Sulcus in the Human Brain: Anatomical Study - Bassam MJ Addas (Journal of King Abdulaziz University: Medical Sciences, 2023)
The objective of this article is to investigate the prevalence of the anterior occipital sulcus in the human brain. The external surface of 25 consecutive formalin fixed brains (50 hemispheres) were examined for the presence of the anterior occipital sulcus. The anterior occipital sulcus was identified in 11 (22%) hemispheres, seven on the right side and four on the left side. The sulcus length ranged from 1-5 cm with a mean length of 2.89 cm. The mean distance from the occipital lobe tip to the anterior occipital sulcus was 4.75 cm on the right side and 5 cm on the left side. The anterior occipital sulcus can be infrequently encountered in human brains (22%); when present it represents the posterior limit of the temporal lobe and the anterior limit of the occipital lobe.